Analisis Kebijakan Vaksinasi Rabies Ditinjau Dari Aspek Perspektif Masyarakat Pemilik Hewan Di Kota Payakumbuh - Riche Hanny Z; Perengki Susanto (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Rabies is a fatal zoonotic disease and remains a public health threat in various regions, including Payakumbuh City. Vaccination of pets is a key strategy in rabies prevention efforts. This study aims to: (1) explore pet owners' perceptions of the effectiveness and implementation of the rabies vaccination policy in Payakumbuh; (2) identify factors influencing community attitudes and behaviors toward the vaccination policy; (3) determine barriers to vaccination implementation; and (4) provide policy recommendations from a community perspective. This study employed a quantitative approach with a descriptive-analytic design. The theoretical framework used is the Health Belief Model (HBM), comprising six HBM constructs and eight sociodemographic variables as independent variables. Data were collected from 200 respondents and analyzed using binary logistic regression. The results of the multivariate analysis indicate that the variable of self-efficacy significantly affects vaccination decisions (p = 0.003; Exp(B) = 2.235). Among the sociodemographic variables, the purpose of animal husbandry significantly impacts vaccination decisions (p = 0.028), and specifically, the purpose of husbandry for home protection shows a lower tendency towards vaccination (p = 0.021; Exp(B) = 0.235). These findings suggest that rabies vaccination behavior is influenced by a combination of individual perception factors and social characteristics.